1995
DOI: 10.1002/j.1550-8528.1995.tb00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy Homeostasis, Autonomic Activity and Obesity

Abstract: Obesity is often accompanied by alterations in both sympathetic and parasympathetic autonomic functions. The present paper summarizes the results of a number of studies designed to investigate autonomic functioning in normal, genetically, and experimentally obese rats. Particular emphasis is given to autonomic functioning and dysfunctioning in relation to the processes that are involved in the regulation of peripheral energy substrate homeostasis. It is concluded that alterations in autonomic regulation in obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This result is probably because of the narrow range of maximal oxygen uptake, and the relationship between HR recovery and metabolic syndrome was persistent even after maximal oxygen uptake was forced into a multiple regression model (data not shown). Obesity, an important component of metabolic syndrome, is characterized by autonomic dysfunction in the parasympathetic system ( 12 , 22 ), which can be lessened by weight loss ( 23 ). There is also good evidence that the parasympathetic nervous system participates in the release of free fatty acids, thereby influencing insulin sensitivity and fat synthesis ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result is probably because of the narrow range of maximal oxygen uptake, and the relationship between HR recovery and metabolic syndrome was persistent even after maximal oxygen uptake was forced into a multiple regression model (data not shown). Obesity, an important component of metabolic syndrome, is characterized by autonomic dysfunction in the parasympathetic system ( 12 , 22 ), which can be lessened by weight loss ( 23 ). There is also good evidence that the parasympathetic nervous system participates in the release of free fatty acids, thereby influencing insulin sensitivity and fat synthesis ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the autonomic nervous system plays a crucial role in the development of obesity and prevents further weight gain through energy substrate homeostasis [21][22][23] . However, previous studies concerning autonomic nervous system activity in obese adults have produced conflicting results 24) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to maintain normal weight from childhood. Moreover, because it is known that diet therapy and physical training could reduce the level of sympathetic nerve activity in obesity 21,30) , these lifestyle modifications might be beneficial for preventing obese children from future morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%